Applications of Flexible Bronchoscopy in Infants with Congenital Vocal Cord Paralysis: A 12-Year Experience - Chien-Hung Kuo; Cheng-Kuang Niu; Hong-Ren Yu; Mei-Yung Chung; Chung-Feng Hwang; Kao-Pin Hwang (Elsevier, 2008)
Congenital vocal cord paralysis (VCP) is a common cause of congenital stridor. Before the widespread application of flexible bronchoscopy (FB) by pediatricians, congenital stridor in infants was usually attributed to laryngomalacia. Prompt recognition and careful follow-up is crucial for the management of congenital VCP. Methods: We performed a retrospective chart review of newborn infants with congenital VCP diagnosed by FB over a 12-year period. Results: During the 12-year period, FB was performed on a total of 356 infants. Fifteen (4%) infants were diagnosed with congenital VCP. There were eight males and seven females and the mean age at diagnosis was 76.6 days. Stridor with respiratory distress was the most prominent presenting symptom. The majority (93%, 14/15) demonstrated bilateral VCP, while one patient (7%) had unilateral VCP. Seven of the 15 (46%) patients had idiopathic VCP, while eight (54%) had VCP associated with neuromuscular disorders. Tracheotomy was necessary in four patients (26%). None of them underwent further surgical interventions. Spontaneous recovery occurred in 10 patients (71%), and of these, 90% (9/10) were treated without tracheotomy. Conclusion: In order to allow prompt diagnosis of congenital VCP, FB should be performed in every newborn infant with stridor. Patients with congenital VCP should undergo additional imaging studies to detect any associated neurological abnormalities and intrathoracic comorbidities. The majority of patients can be managed conservatively and monitored carefully using serial FB. Corrective surgery should be reserved for those with a lack of resolution at prolonged follow-up, and those with significant comorbidities.